The Tree of Prohibition and the Theology of Limits: Genesis 2:9, 16-17 and Contemporary Eco-Ethical Responsibility - Koko, John Clerk; Mpigi, Goka M. (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2461, 2026)
This study examines the prohibition concerning the tree in the midst of the garden in Genesis 2:9, 16-17 and how this could form a basis for a theology of limit intrinsic to creation. While eco-theological discourse has largely focused on constructive dominion in Genesis 1, this paper contends that the prohibition regarding the tree in Genesis 2 provides a foundational paradigm for understanding creaturely responsibility. Using the methodology of theological exegesis, the study engages key biblical scholars like Walter Brueggemann, Gordon J. Wenham, and Claus Westermann to examine the literary centrality of the tree, the structure of generous permission and singular prohibition, and the anthropological significance of humanity formed from the soil. Their insights illuminate how freedom in the garden is bounded by divine command. In constructive dialogue with Jürgen Moltmann and Sallie McFague, the paper argues that limit is not punitive but constitutive of creatureliness. The tree functions as a visible sign of non-absolute human access, thus grounding ecological responsibility in restraint, relationality, and reverent participation within the ordered creation. Keywords: Ecological crisis, Tree of Prohibition, Theology of Limits, Eco-Theology, Responsibility, and Creatureliness.